The Idea of Freedom in Islamic Thought - Ahmadzai, Ashuqullah; Najrabi, Abdurahman (Integrated Journal for Research in Arts and Humanities, 2022)
From the Islamic point of view, freedom is a fundamental right. And scientifically, it has been placed in a structure that reveals the originality of Islam in expressing this right. Rights that are governed by human values ​​and legislative principles. And it is the inner (inherent) freedom song to the will and authority. And external freedom, which belongs to the collective dimension of man, who known as public freedom which in this Islam originates from human dignity by God and his succession on earth. To have complete freedom to exploit the universe and to be able to conquer and exploit it according to the substitute method which is worship and sovereignty. The Muslim Ummah must know that political freedom, freedom of opinion and ijtihad, freedom of criticism and speech, economic freedom, and all actions are safe for him and as long as he adheres to the right and justice commanded by God. His complete servitude to the Almighty is committed to any freedom, freedom is a genuine human right, and this right will not be violated by anyone unless there is an obstacle in the way. For this reason, the divine religions, which are responsible for educating the population and refining morality, are the most staunch defenders of human freedom! And also, for this reason, the Holy Qur'an is full of verses that establish the freedom of the human will and deny restraint from all desires. Which is mentioned in this discussion. Accompanying forbidding any other duty and calling for obedience and forbidding sin, reward, punishment, reckoning, and punishment, and court and enforcing limits and punishments and other things like that, are all repeated emphases on the issue of human freedom.